2012
DOI: 10.1210/jc.2011-3007
|View full text |Cite
|
Sign up to set email alerts
|

Sex Dimorphism in the Relation between Early Adiposity and Cardiometabolic Risk in Adolescents

Abstract: These data show sexual dimorphism in effects of early life body mass index and fat distribution upon cardiometabolic risk factors. Females in a contemporary population are particularly prone to increased risk when born heavier. This has implications for targeted prevention of obesity and metabolic diseases with increasing maternal obesity and gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 37 publications
5
45
0
1
Order By: Relevance
“…Meta-analysis has shown that obese children compared to their normal weight peers are 3-5 times more prone to hypertension [38]. Obesity is a stronger risk factor for HT in teenage boys than girls [39]. These observations are in agreements with our results, because the blood pressure ≥ c95 was seen in over 16% of the study population.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Meta-analysis has shown that obese children compared to their normal weight peers are 3-5 times more prone to hypertension [38]. Obesity is a stronger risk factor for HT in teenage boys than girls [39]. These observations are in agreements with our results, because the blood pressure ≥ c95 was seen in over 16% of the study population.…”
Section: Discussionsupporting
confidence: 92%
“…Obesity in children is still not considered a factor contributing to the development of many metabolic diseases in the future. An important factor responsible for eating disorders in children is the lack of knowledge about the factors contributing to the health of children [39,46]. These observations are supported by the findings in the population ZG and LE.…”
Section: Discussionsupporting
confidence: 67%
“…Detailed information on measures of blood pressure, anthropometry and biochemistry, is given in detail elsewhere [23,24]. Briefly, blood pressure was measured with an automatic device (Dinamap Vital Signs Monitor 8100, Dinamap XL Vital Signs Monitor or Dinamap ProCare 100; GE Healthcare) after 5 minutes rest and using the appropriate cuff size.…”
Section: Blood Pressure Anthropometry and Blood Samplesmentioning
confidence: 99%
“…Six readings were recorded, and the average value was calculated after excluding the first reading. at Royal Perth Hospital as described previously [23,24].…”
Section: Blood Pressure Anthropometry and Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation